Synthesis and Photocatalytic Activity of Pt-Deposited TiO2 Nanotubes (TNT) for Rhodamine B Degradation - Qiu, Xiaojian; Wan, Zhenning; Pu, Mengjie; Xu, Xiuru; Ye, Yuanyao; Hu, Chunhua (Frontiers in Chemistry, 2022)
Dye wastewater has attracted more and more attention because of its high environmental risk. In this study, a novel TiO2 nanotube (TNT) catalyst was prepared and its morphology and structure were characterized by XRD, SEM/EDX and TEM. The synthetic catalyst was used to degrade RhB under UV light and evaluate its application performance. According to the characterization results and degradation properties, the optimum synthesis conditions were selected as 400℃ calcination temperature and 10 wt.% Pt deposition. As a result, the degradation efficacies were sequenced as TNT-400-Pt > TNT-500-Pt > TNT-400 > TNT-300-Pt. In addition, the effect of pH, initial concentration of RhB were explored, and their values were both increased with the degradation efficacy decreased. While moderate volume of 11 mM of H2O2 addition owned better performance than that of 0, 6 and 15 mM. Scavenger such as tertbutanol (t-BuOH), disodium ethylenediaminetetraacetate (EDTA-Na2) and nitroblue tetrazolium (NBT) were added during the catalytic process and proved that superoxide radical anions (O2–•), photogenerated hole (h+) and hydroxyl radical (OH•) were the main active species contributing for RhB removal. For the application, TNT-Pt could deal with almost 100% RhB, CR, MB and OR within 70 min and still kept more than 50% RhB removal in the fifth cycling use. Therefore, TNT-Pt synthesized in this study has potential to be applied on the dye wastewater treatment.